The Harvard dictionary of music - Randel, Don Michael (Cambridge, Mass. : Belknap Press of Harvard University Press, 2003)
This classic reference work has been brought completely up to date in this new edition. Combining authoritative scholarship and lucid prose, this is the essential guide for musicians, students, and everyone who appreciates music. Includes entries on all the styles and forms in Western music; comprehensive articles on the music of Africa, Asia, Latin America, and the Near East; descriptions of instruments with historical background; and articles that reflect today's beat, including popular music, jazz, and rock. Encyclopedia-length articles by notable experts alternate with short entries for quick reference, including definitions and identifications of works and instruments.--From publisher's description.
Rev. ed. of: New Harvard dictionary of music. 1986.
Includes bibliographical references.
Also issued online.
Keywords: Music -- Dictionaries; Dictionaries